2015
DOI: 10.1021/acsami.5b07029
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Programmed Clusters of Gold Nanoparticles for Cancer Cell-Targeted Photothermal Therapy

Abstract: Interpretations of the interactions of nanocarriers with biological cells are often complicated by complex synthesis of materials, broad size distribution, and heterogeneous surface chemistry. Herein, the major capsid proteins of an icosahedral T7 phage (55 nm in diameter) are genetically engineered to display a gold-binding peptide and a prostate cancer cell-binding peptide in a tandem sequence. The genetically modified phage attracts gold nanoparticles (AuNPs) to form a cluster of gold nanoparticles (about 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 40 publications
(72 reference statements)
0
52
0
Order By: Relevance
“…It can facilitate construction of nanocomposites in optimum size and volume for intended use. In addition, distinct biophysical properties enable metallic NPs to be used in photothermal therapy, computed tomography, and magnetic resonance imaging, allowing them to develop as theranostic nanomedicine, as well as drug‐delivery vehicles . These beneficial features of metallic NPs may be easily adopted into our NNP system with established surface chemistry, and bioconjugation methods.…”
Section: Discussionmentioning
confidence: 99%
“…It can facilitate construction of nanocomposites in optimum size and volume for intended use. In addition, distinct biophysical properties enable metallic NPs to be used in photothermal therapy, computed tomography, and magnetic resonance imaging, allowing them to develop as theranostic nanomedicine, as well as drug‐delivery vehicles . These beneficial features of metallic NPs may be easily adopted into our NNP system with established surface chemistry, and bioconjugation methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Guo et al have recently shown interesting results on the PCa cells PC-3 and LNCaP indicating that two of their investigated formulations with transferrin and folate-receptor targeting ligands respectively (AuNPs-PEG-Tf and AuNPs-PEI-FA) show potential as non-viral gene delivery vectors in the treatment of PCa [141]. The photo-dynamic/thermal technique has also shown some progress recent years for both PCa and BC [156,157,158,159,160,161,162,163,164,165]. For example, Oh et al have shown promising PCa cell killing efficacy by using a 55 nm small icosahedral phage that was engineered to display a gold-binding peptide as well as a PCa cell-binding peptide and applying a 60 mW/cm 2 light irradiation [156].…”
Section: Nanoparticles For Prostate and Breast Cancermentioning
confidence: 99%
“…The photo-dynamic/thermal technique has also shown some progress recent years for both PCa and BC [156,157,158,159,160,161,162,163,164,165]. For example, Oh et al have shown promising PCa cell killing efficacy by using a 55 nm small icosahedral phage that was engineered to display a gold-binding peptide as well as a PCa cell-binding peptide and applying a 60 mW/cm 2 light irradiation [156]. Mkandawire et al have recently investigated an alternative way to treat BC cells inducing apoptosis by targeting their mitochondria using AuNPs during photothermal treatment [164].…”
Section: Nanoparticles For Prostate and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…This ultimately amplifies the photothermal effect in the NIR region [34][35][36]. Inspired by these interesting properties, gold nanoparticle clusters (AuNCs) can be applied as an efficient photothermal agents [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%